Efficacy of sodium-glucose co-transporter 2 inhibitors in treatment of non-alcoholic fatty liver disease: A systematic review and meta-analysis. (August 2022) - Ahmed, Syeda Hoorulain; Moeed, Abdul; Waqar, Eisha; Rizwan, Sahar; Hasnain, Nimra; Qamar, Mohammad Aadil; Fatima, Kaneez; Khan Minhas, Abdul Mannan
Abstract: Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is one of the most common causes of chronic liver disease worldwide. We conducted this meta-analysis to evaluate the efficacy of sodium-glucose cotransporter 2 (SGLT2) inhibitors in treating NAFLD. Methods: Electronic databases were searched until November 2021 for randomized controlled trials. A random-effects model was used to pool continuous outcomes to derive weighted mean difference (WMD) and their 95% confidence intervals (CIs). Results: Sixteen randomized-controlled trials were short-listed. SGLT2 inhibitors significantly decreased Alanine aminotransferase (ALT) levels (WMD: 4.33) and Aspartate aminotransferase (AST) levels (WMD: 3.20) while reducing Gamma-glutamyl transferase (GGT) levels (WMD: 6.96) non-significantly. Fibrosis-4 (FIB-4) index reported a non-significant association (WMD: 0.06), whereas significant reductions in Magnetic Resonance Imaging Proton Density Fat Fraction (MRI-PDFF) percentage (WMD: 2.00) and mean Controlled attenuation parameter (CAP) score (WMD: 17.77) were observed. Abdominal subcutaneous fat area (SFA) (WMD: 21.58) reduced non-significantly, whereas Abdominal visceral fat area (VFA) (WMD: 26.55) reduced significantly. Body mass index (BMI) (WMD: 0.79), body weight (WMD: 2.80), and HbA1C (WMD: 0.28) showed significant decrease. However, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (WMD: 0.50) and fasting plasma glucose levels (WMD: 4.18) decreased non-significantly. Conclusion: There was a significant improvement in the levels of liver enzymes along with liver and body fat composition and glycemic indices with the use of SGLT2 inhibitors. Highlights: NAFLD is a leading cause of chronic liver disease and liver-related mortality. Lipid-lowering properties of SGLT-2 inhibitors help alleviate liver enzyme levels. SGLT-2 inhibitors significantly reduced ALT and AST levels. SGLT-2 inhibitors promote fat metabolism, thereby improving liver histology. SGLT-2 inhibitors have therapeutic potential in treating patients with NAFLD.